The Effect of Green Accounting Dimensions on the Quality of Life of Communities Surrounding Mining Areas: A Panel Data Analysis of Mining Companies in Indonesia (2020–2024) - Ros Nirwana; Adista Anjar Diany; Suzi Suzana; Prio Satrio (Jesya, 2026)
This study examines the effect of environmental, social, and economic dimensions of Green Accounting on the Quality of Life of communities surrounding mining companies in Indonesia. Using purposive sampling, the study analyzes panel data consisting of 95 observations from 19 mining companies over the period 2020–2024. The data are analyzed using panel regression with the Fixed Effects Model (FEM), selected based on model specification tests, and estimated with robust standard errors to ensure reliable results. The findings indicate that environmental performance has a positive and significant effect on Quality of Life, while social and economic performance do not show significant effects. The model explains 44.58% of the variation in Quality of Life, indicating a moderate explanatory power. These results suggest that environmental practices provide more direct and measurable impacts on community welfare compared to social and economic initiatives. This study contributes to the literature by providing empirical evidence that the effectiveness of Green Accounting dimensions is not uniform, where environmental aspects play a more dominant role in improving Quality of Life. The findings also extend Stakeholder Theory and Legitimacy Theory by highlighting that corporate environmental responsibility is more strongly associated with stakeholder welfare and social legitimacy than other dimensions. From a policy perspective, the results imply that mining companies and regulators should prioritize environmental performance as a key driver of community welfare, while improving the effectiveness and targeting of CSR programs and economic contributions to generate more tangible social impacts.